METHODOLOGY FOR SELECTING CHILDREN IN GROUPS OF INITIAL TRAINING IN SWIMMING - Darvish, T.A.; Kugusheva, T.V.; Galanova, S.S.; Baklakova, M.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to study the effectiveness of the methodology for selecting children of seven to eight years old in the group of initial swimming training, supplemented by a block of psychological and pedagogical assessment of personal qualities. Methods and structure of the study. The study involved children aged seven to eight years who wished to go in for swimming, the total composition of the subjects was 16 people. To achieve the goal, the following blocks were studied and evaluated: the physical fitness of young swimmers, psychological and pedagogical assessment, and testing was carried out to identify the level of motivation for swimming (based on the “Ladders of motives” by A.I. Bozhovich, I.K. Markova). Results and conclusions. It was revealed that the distinctive features of the content of the experimental methodology for selecting children of seven to eight years old in the group of initial training in swimming is the addition of a block of psychological and pedagogical assessment, based on the assessment of personal qualities (type of temperament, psychotype) and characterizing the predisposition and readiness of children for swimming lessons. According to the identified personal qualities, the most promising children of seven to eight years of age, when selected for the group of initial training in swimming, are children with a sanguine or phlegmatic temperament type, and introverts according to their psychotype. Young swimmers who passed the selection according to the experimental method feel the need to personally achieve high results, participate in competitions, while in children of the control group, the motives are mainly based on the recognition and approval of others (parents, comrades, coaches).